Mechanical and Thermal Properties of Calcined Clay Mixed with Agrowaste Char for Sustainable Building Applications - Benjamin Agyei-Tuffour; Michael E. Sewordor; John Freeman Baffoe; Martha Forson; John Ekow Ampah-Essel; Beatrice Ardayfio; Bashiru Kadiri-English; Kwame K. Marfo; John Adjah; Joshua Tuah Asante; Emmanuel Nyankson; David Dodoo-Arhin (Advances in Materials Science and Engineering)
This paper presents a combined experimental and computational result on the mechanical and thermal properties of calcined clay-agrowaste char composites for sustainable building applications. The calcined clays were characterized for their structural, microstructural, mechanical, and thermal properties after they were mixed with 5 wt%, 10 wt%, 15 wt%, and 20 wt% of agrowaste char of varying sources (i.e., coconut, palm kernel, and acacia). Analytical and finite element analyses were used to predict and also confirm the experimentally determined results. The results show that increasing char fractions increases the thermal energy properties but reduces the mechanical properties. For the compressive strength results, it was noted that the palm kernel char composite recorded the highest compressive strength (∼4.60 MPa) followed by coconut char (∼4.23 MPa) and acacia char composites (∼4.14 MPa). The optical micrographs show uniform distribution of the char in the clay/cement matrix. The analytical and finite element analysis predictions show that the sample with microcracks recorded appreciable fracture toughness (∼38.2 MPa/mm−0.5) and slow rate of energy release during fracture. The implications of the results are discussed to elaborate on the role calcined clays and agrowaste chars plays on the thermal and mechanical properties for a sustainable building materials industry.